Business cycle synchronisation in the ECOWAS region - Ngozi Eunice Egbuna; Maimuna John-Sowe; Santigie M. Kargbo; Sani Bawa; Ibrahima Diallo; Isatou Mendy (West African Monetary Institute (WAMI), 2020)
Countries of the Economic Community of West African States (ECOWAS) are heterogeneous, characterized by marked differences in production and export structures, divergent levels of inflation rates and fiscal positions. These features suggest that there is a greater tendency for the transmission of asymmetric shocks across member countries in the ECOWAS region. Understanding how well business cycles are synchronised between member countries is extremely important in designing appropriate policy responses to facilitate the launch of the single currency and reduce the cost of joining the proposed ECOWAS monetary union. This study undertakes a time-varying assessment of the degree of synchronisation of business cycles among ECOWAS member countries and analyses the role of bilateral trade, financial integration, and convergence in fiscal and monetary policy in achieving more synchronised business cycles in the region. Using the Hausman-Taylor and Error Components panel two-stage least squares (EC-2SLS) estimation techniques over the period 2001 - 2018, this study finds that well-coordinated policy responses such as the strengthening of trade linkages, convergence in fiscal policy and strong financial linkages would foster more closely synchronised business cycles across the region. Thus, measures to promote the synchronisation of business cycles and ensure the sustainable adoption of a single currency should focus not only on satisfying the macroeconomic convergence criteria, but also enhance trade and financial integration to foster broader policy coordination among countries in the region.
Keywords: C33; E32; O55; 330; Business Cycle Synchronisation; Trade Linkages; Financial Integration; ECOWAS